Cover Picture: Highly Conformationally Restricted Cyclopropane Tethers with Three‐Dimensional Structural Diversity Drastically Enhance the Cell Permeability of Cyclic Peptides (Chem. Eur. J. 13/2017). Issue 13 (29th December 2016) - Matsui, Kouhei; Kido, Yasuto; Watari, Ryosuke; Kashima, Yousuke; Yoshida, Yutaka; Shuto, Satoshi
Abstract : Cyclopropane tethers with three‐dimensional structural diversity are able to remarkably change the conformation and physicochemical properties of cyclic peptides due to the characteristic steric feature of cyclopropane. In particular, the introduction of a cyclopropane tether (CPT), cis ‐NfCf fixed the conformation suitable for passive transport and dramatically improved the cell permeability of a model cyclic peptide. More information can be found in the Full Paper by S. Shuto et al. onpage 3034 ff.